Significant Abnormalities Other than Lung Cancer in Korean Lung Cancer CT Screening - Soon Ho Yoon; Junghee Hong; Eui Jin Hwang; Heekyung Kim; Hyun-ju Lim; Young Joo Suh; Hyae Young Kim; Jin Mo Goo (대한영상의학회지, 2019)
A low-dose chest CT is performed for early detection of lung cancer, but the CT scan frequently shows several incidental abnormalities. Identification of the incidental findings may enable early detection of diseases other than lung cancer, thereby improving the survival of the individual undergoing screening. However, insignificant incidental abnormalities may cause unnecessary additional examination and costs. It is crucial for radiologists to appropriately comprehend and report significant incidental abnormalities other than lung cancer for successful implementation of the national lung cancer screening program in Korea.